Salvianolic acid A attenuates steroid resistant nephrotic syndrome through suPAR/uPAR-αvβ3 signaling Inhibition - Li, Xin; Qi, Dong; Wang, Meng-ying; Ji, Kai; Xie, Qun-ling; Wang, Yu; Du, Shi-hao; Fan, Hua-ying (Journal of ethnopharmacology, 2021)
Salvianolic acid A (SAA) is extracted from traditional Chinese medicine Salvia miltiorrhiza and is the main water-soluble and the biologically active ingredient. SAA possesses a variety of pharmacological activities and has an excellent protective effect on kidney disease, especially steroid resistant nephrotic syndrome (SRNS), and has advantages in improving the efficacy of glucocorticoids, but its mechanism needs to be further explored. The study was designed to explore the effect of suPAR and uPAR in SRNS patients and evaluate the potential effect of SAA in improving podocyte steroid resistance and explore its mechanism. The ELISA kits were used to detect the levels of suPAR in the blood and urine of subjects. The levels of uPAR, GRα, and GRβ expression in renal tissues of SRNS patients was detected by immunohistochemistry and analyzed using the Pearson method. In vitro studies, steroid resistance model was induced by the TNF-α and IFN-γ. The protein and mRNA expression of Nephrin, GR, GRα and GRβ were analyzed using western blot and qRT-PCR. The activity of GR-DNA binding was detected by using TransAM™ GR kits. Adriamycin further induced steroid resistance podocyte. Flow cytometry was used to detect the effect of SAA on podocyte apoptosis. ELISA assay was used to detect the suPAR expression in the podocyte supernatant. Western blot and qRT-PCR were used to detect the protein and mRNA expression of uPAR and Nephrin in podocytes. The serum and urine levels of suPAR were conspicuously higher in SRNS patients than healthy volunteers and SSNS patients, and the expression of uPAR in renal tissue of SRNS patients is negatively correlated with GRα, but positively correlated with GRβ. The combination of TNF-α and IFN-γ could conspicuously increase the GRβ expression and reduce GRα/GRβ, and induce steroid resistance in podocytes. Moreover, we found that SAA could reduce the apoptosis of podocytes and suppress the expression of suPAR/uPAR, and increase the expression of Nephrin. The level of suPAR and uPAR expression may have important value in predicting glucocorticoids resistance in patients with idiopathic nephrotic syndrome (INS). The combination of TNF-α and IFN-γ induce podocytes can establish steroid resistance model in vitro. SAA could improve glucocorticoids resistance of podocyte which can be attributed in part to regulate the suPAR/uPAR-αvβ3 signaling pathway. [Display omitted]